2018
DOI: 10.6002/ect.2016.0323
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Prognostic implications of early protocol biopsies have been studied; however, the value of late protocol biopsy in predicting graft outcome has not been well defined. Here, we compared the effects of early and late protocol biopsy histologic findings in stable kidney allografts and aimed to understand the significance of "borderline" rejection on allograft function. Materials and Methods: We studied 261 biopsies from 159 renal transplant recipients who were on a steroidfree, calcineurin inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…It is important for health professionals to attend to these patients from early detection since the costs in the different levels of care for kidney patients are high, aside from how significantly their quality-oflife decreases, both for patients and their family members involved in the process (57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important for health professionals to attend to these patients from early detection since the costs in the different levels of care for kidney patients are high, aside from how significantly their quality-oflife decreases, both for patients and their family members involved in the process (57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…This practice is expensive, but it could contribute to the problem that has developed when this paper was written, in order to identify some causes that have been neglected, which are important in the development of ESRD. The public health system should propose alternatives that help to identify these factors that would undoubtedly assist in explaining a portion of this great problem (58).…”
Section: Discussionmentioning
confidence: 99%
“…Although this allows early detection of rejection and tubular atrophy, the effect on long term graft survival remains unclear. Most studies showed comparable short term results in both patients that had protocol biopsies and those that had biopsies on indication of clinical symptoms (206). However, a recent prospective study revealed children who underwent protocol biopsies to have better renal function on the long term than the control group (205).…”
Section: Graft Biopsiesmentioning
confidence: 99%